2007
DOI: 10.1159/000110457
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin Potentiates Vinblastine Cytotoxicity Through Downregulation of mdr-1 Gene Expression in HepG2 Cells

Abstract: Background: P-glycoprotein (Pgp), produced by multidrug resistance-1 gene (mdr-1), is a main mechanism developed by cancer cells to guard against anti-cancer drugs. Alterations of DNA methylation of the mdr-1 gene promoter are known to be linked to mdr-1 gene expression and are probably related to intracellular S-adenosyl-methionine. We here used HepG2 cells to determine the role of the methionine cycle (through the use of the Methionine-Synthase (MS) cofactor, cobalamin) on mdr-1 gene expression. Methods: Sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…However, there are many arguments against the hypothesis that the increase is merely due to the selective DNA hypomethylation of PrP C gene(s): (i) the increase in SC PrP C levels is concomitant with a marked decrease in SC PrP C -mRNA levels [66]; (ii) it has been shown that Cbl induces the translational up-regulation of methionine synthase [87], a finding that is in some respects similar to our finding that Cbl regulates PrP C -mRNA levels in Cbl target tissues [66]; (iii) no changes in total protein content have been found in the SC of our Cbl-D rats (Riboni and Scalabrino, unpublished results); (iv) Cbl down-regulates the expression of multidrug resistance (mdr)-1 gene, but this effect is independent of the methylation status of the mdr-1 promoter [88]; (v) many vitamins regulate gene expression by means of different mechanisms not involving the degree of DNA methylation [89]; (vi) it has been demonstrated that Cbl-D neuropathy cannot reasonably be attributed to a failure of the methylation and/or synthesis of myelin basic protein in the rat CNS [90,91]; and (vii) rats made Cbl-D by means of total gastrectomy show increased TNF-a [92] and EGF [93] levels of livers 2 months after total gastrectomy, but these levels normalized 4 months after total gastrectomy, although other authors have demonstrated that the hepatic DNA of Cbl-D rats is hypomethylated [94]. The SC PrP C levels of TGX rats show the same trend [66].…”
Section: Discussionsupporting
confidence: 89%
“…However, there are many arguments against the hypothesis that the increase is merely due to the selective DNA hypomethylation of PrP C gene(s): (i) the increase in SC PrP C levels is concomitant with a marked decrease in SC PrP C -mRNA levels [66]; (ii) it has been shown that Cbl induces the translational up-regulation of methionine synthase [87], a finding that is in some respects similar to our finding that Cbl regulates PrP C -mRNA levels in Cbl target tissues [66]; (iii) no changes in total protein content have been found in the SC of our Cbl-D rats (Riboni and Scalabrino, unpublished results); (iv) Cbl down-regulates the expression of multidrug resistance (mdr)-1 gene, but this effect is independent of the methylation status of the mdr-1 promoter [88]; (v) many vitamins regulate gene expression by means of different mechanisms not involving the degree of DNA methylation [89]; (vi) it has been demonstrated that Cbl-D neuropathy cannot reasonably be attributed to a failure of the methylation and/or synthesis of myelin basic protein in the rat CNS [90,91]; and (vii) rats made Cbl-D by means of total gastrectomy show increased TNF-a [92] and EGF [93] levels of livers 2 months after total gastrectomy, but these levels normalized 4 months after total gastrectomy, although other authors have demonstrated that the hepatic DNA of Cbl-D rats is hypomethylated [94]. The SC PrP C levels of TGX rats show the same trend [66].…”
Section: Discussionsupporting
confidence: 89%
“…The activity of P-gp in HepG2 cells was assessed measuring the intracellular content of the fluorescent compound Rh123, which inversely associates with the amount of substrate extruded [23], [29]. It is known that the probe is transported by P-gp and to some extent by BCRP [30].…”
Section: Methodsmentioning
confidence: 99%
“…Repressors of P-gp, including certain antineoplastic agents that act at nuclear receptors [73], or endotoxin [74], cobalamin [50], and atorvastatin [75,76], potentiate the action of substrates; whereas rifampin (rifampicin) [51] and cell stress signals induce P-gp-mediated drug resistance [29,50,75]. Another mechanism for P-gp-related pharmacoresistance to cytotoxic agents is hypothesized to relate to the cell stress signals they induce [52,77].…”
Section: Compounds That Interact With P-gpmentioning
confidence: 99%
“…Upregulation of ABCB1 gene expression can occur at gene promoter sequences through transactivation [10,47,78], for example, by the pregnane X receptor ( NR1I2 ) gene in response to substrates that may have overlapping specificity for P-gp [29]; or induction can occur independent of nuclear receptors [79]. Alternatively, epigenetic inactivation of P-gp can occur by DNA methylation at specific nucleotide sequences within the promoter sequence, called CpG islands, as has been observed in some cancer tissues [80]; or downregulation of P-gp can also occur by mechanisms other than by DNA methylation, for example, in response to cobalamin, a vitamin B-12 derivative [50]. …”
Section: Compounds That Interact With P-gpmentioning
confidence: 99%